Experimental study for evaluation the efficiency of some traditional and nano-composites materials consolidates to improve the archaeological limestone properties - Mohsen M. Saleh; M. Ezzat; Fatma M. Shebl (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Archaeological limestone artifacts are subject to several deterioration factors that can cause harm while they are buried in soil, such as wet salt soil. Thus, one of the biggest challenges is restoring limestone artifacts that have been discovered from excavations. Understanding the nature of limestone after extraction and the resulting alterations, such as the stone’s structural instability and the high salt content of the artifacts, are prerequisites for the restorer. In 1974 AD, King Ramesses III’s gate was excavated from the ancient Heliopolis Temple in Cairo. The stones were removed from the soil and left on display outdoors at the same excavation site, where they were subject to seasonal variations in temperature and environmental changes. The main objective of the research is to select the best consolidating materials suitable for the pieces of limestone stone artifacts discovered from archaeological excavations due to their special nature, which affects them as a result of their presence in burial soil for long time. Selecting appropriate consolidating materials with appropriate characteristics was important. In order to withstand a range of environmental circumstances. The characteristics of the ancient stones at the King Ramesses III Gate site were investigated and analyzed to ascertain their true state, and their percentage of damage was calculated by contrasting them with the identical natural limestone that had not been subjected to any harmful influences. After that, experimental samples were used, and the efficacy of the treatment materials was assessed. Result Experimental study aims to evaluate the effectiveness of some traditional and nano composites materials to improving the properties of stone artifacts extracted from archaeological excavations. Three consolidating solutions were used as follows, paraloid B72 dissolved in acetone 3%, and Calcium hydroxide nanoparticles dissolved in paraloid polymer with acetone at concentrations of 1% and 3%, in addition to nano calcium carbonate dissolved in paraloid polymer with acetone 1% and 3%. The efficiency of the consolidate materials were evaluated using a scanning electron microscope SEM, as well as measuring the water contact angle, in addition to color change testing and measuring the physical and mechanical properties. Conclusion Nano materials are considered better than paraloid B72 as a consolidated material and the best outcomes results were obtained with a nano calcium carbonate dissolved in paraloid polymer with acetone 3%. Graphical abstract